EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KELENGKENG (Euphoria longan L.) DI KECAMATAN LASALIMU KABUPATEN BUTON - NURFAUZI, FIRDA; ZULFIKAR, ZULFIKAR; HEMON, M. TUFAILA; SYAF, HASBULLAH; NAMRIAH, NAMRIAH; ALAM, SYAMSU (Jurnal Agroteknos, 2022)
This study aims to determine the land suitability class and efforts to manage the limiting factors that exist on land in Lasalimu District, Buton Regency. The method used is an independent survey by taking soil samples in each land unit (LU) for analysis in the laboratory. The results showed that the longan plant was quite suitable (S2) to be developed at LU 25 and 27 with a land area of 65.69 ha (0.95%), marginally suitable (S3) at LU 1-3, 5, 8-14, and LU 23 with a land area is 1,828.10 ha (26.50%), and is not suitable (N) at LU 4, 6, 7, 15- 22, 24, and LU 26 with a land area of 5,004.71 (72.55%). Potentially if efforts are made to manage the limiting factors for the development of longan plants, the suitability class becomes quite suitable (S2) at LU 3, 5, 8-14, 23, 25 and LU 27 with a land area of 1,207.54 (17.49%), marginally suitable (S3) on LU 1, 2, 4, 15, 17, 19- 22, 24 and LU 26 with a land area of 4,787.76 (69.29%) and not suitable (N) on LU 6, 7, 16, and LU 18. Management actions that need to be taken for limiting factors of nutrient availability are fertilization, nutrient retention by liming and adding organic matter, erosion hazard with conservation efforts such as planting according to contours, making terraces and planting cover crops, while for limiting factors such as air temperature, soil depth, slope, surface rocks and rock outcrops cannot be repaired because the limiting factor is permanent